Features Of Emotions in The Upbringing of Children - Kurbonova Nargiza Samadovna; Maxamadiyeva Muxlisa O’tkir qizi (Academia One Publishing, 2024)
This article provides information on the specific features and types of emotional experiences in children and their psychological impact on the upbringing of children
Keywords: empathy; emotion; sympathy; the phenomenon of sympathy empathy